Case Report: Identifying Andersson-Like Lesions in Diffuse Idiopathic Skeletal Hyperostosis - Sun, Xiaojiang; Qiao, Han; Cheng, Xiaofei; Tian, Haijun; Shen, Kangping; Jin, Wenjie; Liu, Xingzhen; Wang, Qiang; Miao, Yiming; Xu, Yue; Zhao, Changqing; Zhao, Jie (Frontiers in Endocrinology, 2021)
Andersson lesions (ALs) in ankylosing spondylitis (AS) serve as a severe risk to ankylosed spine stability, which might result in significant deterioration of spinal cord function after traumatic or inflammatory causes. Herein, erosive discovertebral lesions in diffuse idiopathic skeletal hyperostosis (DISH) presented important clinical similarities to AL in AS but failed to completely recognize unstable spinal lesions. Therefore, we pioneered to identify spinal discovertebral lesions similar to Andersson-like lesions (ALLs) in DISH, followed by the characterization and summarization of etiology, radiology, laboratory results, clinical symptoms and treatment strategies for AL in AS with ALL in DISH. By characterizing ALL in DISH cases, we showed that the ALL was mainly traumatic and established at the junction of focal stress between two adjacent ossified level arms. Erosive discovertebral ALLs were formed after trivial stress of direct impact and could be subdivided into transdiscal, transvertebral, and discovertebral types radiologically. Patients who presented with ALL frequently suffered from consistent back pain clinically and experienced a decrease in motion ability that could reflect skeletal stability, which received treatment effectiveness after conservative external spinal immobilization or further surgical internal fixation, indicating the significance of recognizing ALL in the ankylosed DISH spine to further maintain spinal stability to prevent catastrophic neurologic sequelae. Our work highlighted the clinical relevance of ALL in DISH in comparison with AL in AS, which provided broader insight to identify ALL in DISH, thus facilitating early intervention against DISH deterioration.